Trust & Social Intercultural Legitimacy - IM89 - 202302 - Mackelmann Roedenbeck, Mathias (2023)
In a world where globalization and interculturality prevail inside and outside organizations, it is necessary for students to recognize the relationships between diverse cultural and national identities, as well as the diversity of their modes of communication. Intercultural communication is crucial to comprehending the world today and participating in the world of tomorrow in an increasingly interconnected world. Individuals interact without borders; companies and organizations engage in business on a global scale; and governments respond to public pressures on an international level. Therefore, the communication professional must assume a greater knowledge of the interrelations, greater empathy, and better criteria about the possibilities of communication and its effectiveness. The global era has stimulated transnational cultural flows (of people, practices and products) and local cultural complexities that were inconceivable even a generation ago. Today, it is necessary to function effectively in culturally diverse contexts ranging from organizations and workplaces, neighborhoods, cities, societies and regions. Therefore, intercultural awareness and communication skills are an advantage in many areas of employment, providing communication competencies required in the multicultural, networked world. At the end of the course, the student will develop an essay on how globalization affects organizations and how they apply intercultural communication strategies to maintain effective communicative. Course aim: Theory-based specialization course of the Communication Faculty aimed at students in the tenth cycle, which seeks to develop the general competence of information management and the faculty competence of analysis and interpretation of reality, both in level three. At the end of the course students should demonstrate - through an informed and critical argument - their knowledge and understanding of the key elements of intercultural thinking and be encouraged to engage 1critically with the default large culture approach to culture, cultural difference and intercultural communication.